Vocal information and the navigation of social decisions in bats: Is social complexity linked to vocal complexity?. (27th July 2019) - Knörnschild, Mirjam; Fernandez, Ahana Aurora; Nagy, Martina
Abstract: To make adaptive behavioural decisions, animals must acquire and process information from their natural and social environment. Reducing uncertainty regarding the actions and goals of conspecifics is especially important for group‐living animals. Bats are often highly gregarious and use versatile social vocalizations to mediate social interactions. These social vocalizations encode a substantial amount of ecologically relevant information, such as individual identity, sex and kin. Decoding this information enables receivers to make informed decisions on resource allocation, mate choice, territorial defence and cooperation. Erroneous decisions on such crucial aspects of bats' social behaviour can be costly due to reduced reproductive success or survival. Increasingly complex social interactions require social vocalizations encoding more information which, in turn, could facilitate the evolution of even more complex social interactions. Evidence for the positive correlation of social and vocal complexity is available for several taxa but is currently very limited for bats. We conducted a phylogenetic comparative analysis to link the information content encoded in bats' social vocalizations to the complexity of their social lives, that is the level of uncertainty associated with assessing individual identity. We focused on three different vocalization types encoding individual signatures (pup isolation calls, adult contact calls and male‐specific vocalizations). Information content in bit (i.e. the number of binary decisions necessary to discriminate among N individuals) was used as an estimate of vocal complexity; relevant social group size (i.e. the number of conspecifics whose identity a receiver could confuse) was used as an estimate of social complexity. Our phylogenetic comparative analysis detected a positive relationship between the information content of vocalizations and the respective relevant social group size. This relationship suggests a positive feedback loop between social and vocal complexity for bat vocalizations and highlights the importance of vocal information for negotiating fitness‐relevant social decisions of bats. In conclusion, our work suggests that social complexity drives vocal complexity in bats. Future studies on other hitherto understudied taxa are necessary to establish a comprehensive theory on the multi‐faceted co‐evolution of sociality and communication in the animal kingdom. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.